Beberapa Catatan Mengenai Hama Baru: Penggulung Daun Teh Siput Tanpa Cangkang, Parmarion pupillaris - Bambang Rahayu T. P.; Siwi Indarti; Tri Harjaka (Universitas Gadjah Mada, 2000)
In the past tea plantation at Pagilaran estate is attacked by leaf roller pests. These are Homona coffearia, Cydia leucostoma, and Gracilaria theifora. At present a slug Parmarion pupillaris is found and considered as a new leaf roller pest, because they live inside of the rolled leaf. This symptom is not known before. The population of Parmarion slug is high 3-4 slugs per bush of tea at the sub-division of Pagilaran estate of Pagilaran, Binorong and Garjito. This condition maybe supported by the weather that Pagilaran estate have a high rainfall of 4,842-6,067 mm per year with only 1-2 months of dry season.